2019
DOI: 10.1142/s0219649219500345
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Sharing Concept, Attitude and Influencing Factors: A Case with Indian Academic Librarians

Abstract: The objective of the study is to examine the librarians’ attitude towards knowledge sharing including its concept, potential benefits, communication channels, and influencing factors that may motivate or hinder knowledge sharing practices in academic libraries in India. A questionnaire was used for data collection, 91 LIS professionals from Indian academic libraries were surveyed. In addition, 10 in-depth interviews were conducted. The findings of the study show that understanding of knowledge sharing concepts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Previous studies have identified a substantial correlation between a person’s commitment to their profession and willingness to share their expertise ( Chen et al, 2020 ; Zada et al, 2021 ). Additionally, KS may be nurtured and developed if employees have developed favorable attitudes and gestures toward an organization, which requires a lot of internal desire ( Khan and Ali, 2019 ; Tahir et al, 2019 ). Ethical leaders play an important role in shaping and assisting the professional lives of their workers so that they can participate in KS behavior ( Kuenzi et al, 2019 ).…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…Previous studies have identified a substantial correlation between a person’s commitment to their profession and willingness to share their expertise ( Chen et al, 2020 ; Zada et al, 2021 ). Additionally, KS may be nurtured and developed if employees have developed favorable attitudes and gestures toward an organization, which requires a lot of internal desire ( Khan and Ali, 2019 ; Tahir et al, 2019 ). Ethical leaders play an important role in shaping and assisting the professional lives of their workers so that they can participate in KS behavior ( Kuenzi et al, 2019 ).…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…Paroutis and Al Saleh (2009) performed qualitative study followed by interviews of IT professionals and document review in a multi-national firm to discourse barriers to employees' willingness to use and/or contribute their knowledge to web 2.0 platforms. Subsequently, Kumaresan and Swrooprani (2013), Nazim and Mukherjee (2013), Khan and Ali (2019) discussed attribute, attitude and perceptions hindering KS among librarians. Similarly in KS partnerships, the role of learning partner (organization) is very important to gain shared benefits vis-à-vis taking adequate measures to solve hindrance, enhance monitoring and performance evaluation.…”
Section: Existing Studies On Knowledge Sharing (Ks) Barriersmentioning
confidence: 99%